Investigation of the effects of diisobutyl phthalate on rat testicular tissue: a histopathological and morphometric evaluation - BAŞIMOĞLU KOCA, Yücel (Academia Journal of Biology, 2024)
Phthalates are a group of chemicals used to make plastics more durable, and they are often called plasticisers. Additionally, these chemicals are found in hundreds of products such as floor coverings, lubricating oils, and personal care products (soaps, shampoos, hair sprays). Consumer products containing phthalates can result in human exposure through direct contact and use, indirectly through leaching into the other products or general environmental contamination. In this study, the effects of Diisobutyl phthalate a commonly used phthalate, were investigated histopathologically and morphometrically to determine whether it is one of the causes of increased infertility in recent years. Two study groups of albino Wistar albino rats (total n: 40) were formed; the control group (untreated control group, solvent-corn oil the control group) and the experimental group. DiBP was administered by oral gavage to the experimental group in 3 different doses (0.25–0.5–1 mL/kg/day) mixed with corn oil every day for 28 days. At the end of the experiment, testicular tissue samples taken from all the experimental and control animals were evaluated histopathologically and morphometrically by light microscopy after routine preparation. Degeneration/atrophic tubules were quite prominent in the sections. Tubules containing degenerated germ cells and tubules devoid of germ cells were observed. It was determined that in most tubules, only tubules covered with Sertoli cells remained due to germ cell death. In addition, multinucleated giant cells were frequently encountered in such tubules. Dilatation and thickening in the basal lamina of the seminiferous tubule were accompanied by decreased PAS-positive reaction. The morphometric results supported the histopathological findings. Significant dose-related morphometrical changes (p<0.0001), including seminiferous tubule diameter, tubular lumen diameter, spermatogenic cell line height and basal lamina thickness were observed between the control and administration groups. According to the control, sham and G1, the number of these multinucleated cells (MGC) increased in G2 and G3 but these increases were statistically insignificant (p > 0.9999). In conclusion, it was observed that irreversible damage occurred in the testicular tissues of DiBP-exposed groups, and it was decided that this could be the cause of infertility. Therefore, we recommend the use of an alternative plasticiser with proven reliability.